Prevalence and Factors associated with Anxiety among Uncontrolled Hypertensive Patients in Public Health Centers in Lhokseumawe, Aceh, Indonesia - Rahayu, Mulyati Sri; Wahyuni, Sri (Althea Medical Journal, 2023)
Background: Patients with hypertension frequently experience intense emotions in addition to the physiological effects of the disease, which tend to increase the risk of developing mental health issues such as anxiety. However, the connection between hypertension and anxiety remains uncertain. This study aimed to evaluate the prevalence and factors associated with anxiety in uncontrolled hypertensive patients in public health facilities.Methods: This cross-sectional study was conducted in four public health centers in Lhokseumawe City, Aceh Province, Indonesia. Subjects were selected using consecutive sampling. Data on sociodemographic factors and comorbid conditions were obtained. Blood pressure was recorded, and severity was classified according to the JNC-7 guidelines. The Hamilton Rating Scale for Anxiety (HRS-A) was used to detect anxiety in each participant. Data were analyzed using used the chi-square test.Results: Of 60 respondents, consisting of men (31.7%) and women (68.3%), 34 (56.7%) had mild anxiety, 22 (36.7%) had moderate anxiety, and 3 (5%) had severe anxiety. There was a significant association (p = 0.007) between anxiety and duration of hypertension. On the contrary, no association in age, gender, level of education, and type 2 diabetes comorbidities (p> 0.05).Conclusions: Anxiety is common among hypertensive patients in primary healthcare settings and is associated with the duration of hypertension. Primary care physicians must be on the front lines in finding anxiety disorders, and making the necessary referrals or therapy.